2015
DOI: 10.1631/jzus.b1400259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reducing dietary protein on the expression of nutrition sensing genes (amino acid transporters) in weaned piglets

Abstract: Abstract:The effects of crude protein (CP) levels in the diet on the mRNA expression of amino acid (AA) transporters were studied in a 45-d trial. Eighteen piglets with an initial body weight (BW) of 9.57 kg were assigned to three groups (14%, 17%, and 20% CP in the diet) in a completely randomized design (six replicates per treatment). Diets were supplemented with crystalline AA to achieve equal standardized ileal digestible contents of Lys, Met plus Cys, Thr, and Trp, and were provided ad libitum. After 45 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 35 publications
4
25
0
1
Order By: Relevance
“…Eighteen piglets (initial body weight (BW) is (9.57±0.64) kg) were randomly assigned to three groups. Diets with 20%, 17%, and 14% CP were based on the National Research Council (NRC) recommendation (Committee on Nutrient Requirements of Swine, National Research Council, 2012), as shown in Table 1, and were supplemented with 4 essential amino acids (Lys, Met, Thr, and Trp) to meet the requirements of weaned piglets (Wu et al, 2015). Piglets were housed individually in cages and had free access to drinking water and their respective diets throughout the 45-d experimental period (35 to 80 d of age).…”
Section: Animals and Experimental Treatmentsmentioning
confidence: 99%
“…Eighteen piglets (initial body weight (BW) is (9.57±0.64) kg) were randomly assigned to three groups. Diets with 20%, 17%, and 14% CP were based on the National Research Council (NRC) recommendation (Committee on Nutrient Requirements of Swine, National Research Council, 2012), as shown in Table 1, and were supplemented with 4 essential amino acids (Lys, Met, Thr, and Trp) to meet the requirements of weaned piglets (Wu et al, 2015). Piglets were housed individually in cages and had free access to drinking water and their respective diets throughout the 45-d experimental period (35 to 80 d of age).…”
Section: Animals and Experimental Treatmentsmentioning
confidence: 99%
“…A reduction in dietary crude protein (CP) levels can reduce diarrhea and nitrogen (N) excretion and repair digestive and immune function by enhancing the gene expression levels of digestive enzymes and amino acid (AA) transporters in young pigs [4,6]. For weaned pigs, it has been suggested that the CP levels in their diets can be reduced by 2-3 points without affecting average daily gain (ADG) [4,6], feed efficiency, or gastrointestinal health when the diets are supplemented with AAs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in dietary crude protein (CP) levels can reduce diarrhea and nitrogen (N) excretion and repair digestive and immune function by enhancing the gene expression levels of digestive enzymes and amino acid (AA) transporters in young pigs [4,6]. For weaned pigs, it has been suggested that the CP levels in their diets can be reduced by 2-3 points without affecting average daily gain (ADG) [4,6], feed efficiency, or gastrointestinal health when the diets are supplemented with AAs [7,8]. However, reductions exceeding 3 points have produced no effects on ADG, feed efficiency and the mRNA levels of digestive enzymes (including trypsinogen, chymotrypsin B, and dipeptidase-II and III) and AA transporters [2,4,[9][10][11][12][13], although these trends have not been observed in all studies [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia emissions in the piggery are mainly generated from surplus nitrogen. Therefore, reducing dietary crude protein, which provides the basic requirement for TP intake, and supplementing with synthetic amino acids will significantly decrease NH 3 emissions (Hayes et al, 2004;Cho et al, 2008;Wu et al, 2015). Modulating dietary composition to reduce NH 3 emission is economic and feasible, and the most important thing is that it is performed at source.…”
Section: Discussionmentioning
confidence: 99%